EFEKTIVITAS PERLINDUNGAN HUKUM TERHADAP PERAWAT DALAM MEMBERIKAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RSUD Dr. SOEDIRMAN KEBUMEN - Kasih Pujiutami (Jurnal Idea Hukum, 2018)
Nursing have role and strategies function in halty service for public and need be guaranteed too protection often expererence happen emergency circun stances to emergency measures should do not outharity for sake patient safety, will but malpractice pre sumption and low looking.            Constitution no thirty eight two thousand eighteen year  about nursing for realize effetiveness low protection for nurse give nursing. Care by low research and discusion title is know noget effective because code ethics nursing portially basic profession require delegation of outhority for profession with besidesnurse mush do with write. outhority from proffesion with besides nurse because no get is low a wareness good nurse even nurse commission   Dr soedirman  haspital